Penatalaksanaan Terapi Latihan Pada Pasien Paska Operasi Pemasangan Plate And Screw Pada Frakture Antebrachii 1/3 Proximal - Melati, Rima, Wahyuni, S. Fis. SKM, M.Kes (2015)
Background: Bone fracture is a break continuitas. Antebrachii fracture is a fracture in the forearm radius and ulna. Divided into three parts, namely the proxsimal fracture, medial and distal from the corpus of the bone. Conditions can be given actions fracture with conservative and operative technique, conservative techniques typically use a cast while operatis action is usually performed by ORIF (Open Reduction Internal Fixation). This condition will usually cause pain, edema, limitation of LGS, decreased muscle strength and functional ability. Objective: To determine the benefits of exercise therapy with static contraction technique, free aktive exercise and passive exercise in reducing pain, decreasing edema, increase LGS, increase muscle strength and improve activities. Results: From the results it can be concluded therapy to decrease pain VDS of T1 to T4 can be seen, tenderness T1: 6 to T4: 5, pain motion T1: 6 to T4: 5, painful silence T1: 1 to T4: 0. Decrease edema, 5 cm above the left side T1: 27 cm to T4: 26, 5 cm down the left side T1: 26 to T4: 25. Increased LGS with goneometer with the results, actively T1: S (0-0-40), became T4: S (0-0-45), passively T1: S (0-0-45) into T4: S (2 -0-50). Increased muscle strength with MMT showed, elbow flexors T1: 3 to T4: 4, extensor elbow T1: 3 to T4: 4, pronator T1: 3 to T4: 4 and supinator T1: 3 to T4: 4. Conclusion: Therapeutic exercise in the form of static contraction, free aktive exercise and passive exercise can reduce edema, pain LGS boost, increase muscle strength and improve functional ability.